ANALISIS KONSEPTUAL TEACHING AT THE RIGHT LEVEL DALAM STRATEGI PEMBELAJARAN PPKN - Weni Adenia; Zaskia Naila Nurjanah; Juliana Harahap; Nayla Dwi Ambartika; Evi Susilawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Teaching at the Right Level (TaRL) is a pedagogical approach that focuses on adjusting instructional practices to learners’ actual levels of competence in order to accommodate variations in students’ learning abilities. In Civic Education (PPKn), instructional difficulties frequently occur due to differences in students’ levels of comprehension, civic engagement, and participatory skills. This study seeks to conceptually examine the relevance and potential application of Teaching at the Right Level as a learning strategy within PPKn instruction. The research adopts a library-based approach by analyzing books, national and international scholarly articles, as well as policy documents related to TaRL and PPKn learning. Data analysis was conducted through content analysis to explore essential concepts, core principles, and the implications of implementing TaRL in PPKn learning contexts. The results suggest that Teaching at the Right Level is compatible with the fundamental characteristics of PPKn learning, particularly in fostering student-centered instruction, educational equity, and differentiated learning practices. From a conceptual perspective, TaRL demonstrates strong potential to enhance civic understanding, learner participation, and character development when utilized as a strategy in PPKn education. This study offers a theoretical contribution by proposing a conceptual basis for integrating Teaching at the Right Level into PPKn learning practices.